ASSESSING VINEYARD RISKS: THE EFFECTS OF CLIMATE CHANGE ON GRAPE CULTIVATION IN MADEIRA, PORTUGAL - Pereira, Julia Martins (Ayden Journal of Agriculture and Allied Studies, 2024)
Grapevines, belonging to the Vitaceae family, are of paramount significance in the world of viticulture. This family encompasses a diverse array of species, predominantly tropical or subtropical, spanning across 14 to 16 genera and comprising over 900 species. Within the Vitis genus, we encounter a notable diversity of 80 species classified into two subgenera: Muscadinia and Euvitis. The Euvitis subgenus, particularly, garners attention as it encompasses three distinct groups—American, Asian, and Eurasian. The Eurasian group, dwelling in the Mediterranean basin, holds global prominence in viticulture, with widespread distribution in temperate regions of Europe, North America, and Asia. These grapevines undergo an annual developmental cycle, encompassing nine distinct growth stages, commencing from bud break and culminating in leaf fall, heralding winter dormancy. The productivity of grapevines hinges on the interplay of genetic attributes specific to vine varieties and the influence of agroecological factors on the phenological phases of development. This paper delves into the intricate world of grapevines, their taxonomic diversity, and annual growth cycle, shedding light on the pivotal factors that shape their productivity.